The Borderline symptom list-interview: development and psychometric evaluation of an observer-based instrument for assessing symptom severity in borderline personality disorder - Senyüz, Büsra; Vonderlin, Ruben; Claus, Carola; Mahalingam, Saskia; Koch, Stefan; Voderholzer, Ulrich; Teismann, Tobias; Kleindienst, Nikolaus; Böhnke, Jan R.; Lis, Stefanie; Boritz, Tali; McMain, Shelley; et al. (Borderline Personality Disorder and Emotion Dysregulation, 2025)
Borderline Personality Disorder (BPD) is a complex mental health condition characterized by pervasive instability in mood, interpersonal relationships, self-concepts, and behavior. A reliable assessment of BPD symptom severity is essential for effective treatment planning and evaluation. This study introduces and evaluates the Borderline Symptom List Interview (BSL-I), a semi-structured interview designed to assess the severity of BPD symptoms comprehensively. The BSL-I is a freely accessible 31-item interview designed to assess BPD symptom severity. It evaluates (a) the frequency and subjective distress associated with BPD-specific and typical psychopathological symptoms, (b) the behavioral consequences of these symptoms, (c) functional impairment, and (d) facets of positive mental health. The items were developed through an iterative process, incorporating feedback from international experts and individuals with lived experience of BPD. Psychometric properties of the BSL-I were examined cross-sectionally in different samples of clients meeting DSM-5 criteria for BPD (n = 171), clinical controls (n = 89), and healthy controls (n = 43). The BSL-I demonstrates good internal consistency within the BPD sample (Cronbach’s α = 0.82) and good interrater reliability (ICC = 0.768). It significantly discriminates between BPD clients and clinical controls (Cohen’s d = 2.02) and healthy controls (Cohen’s d = 3.88). High correlations were observed with other established BPD symptom measures, including the number of IPDE criteria (r = 0.70, p < 0.001) and the BSL-23 (r = 0.83, p < 0.001). Our findings indicate that the BSL-I is a reliable and valid multidimensional instrument for assessing the severity of BPD. Both clinical experts and clients found the application of the BSL-I acceptable and feasible. Future research might explore its sensitivity to change resulting from psychosocial treatments and assess its utility for treatment planning and outcome measurement. The BSL-I is a practical and psychometrically sound instrument for assessing the severity of BPD symptoms in clinical and research contexts.
Gesehen am 10.11.2025